Landslide Risk Assessment. - Lee, E. Mark (Institution of Civil Engineers, 2013)
In this second edition new information is included on pipelines, deepwater oil and gas, and remote sensing imagery with GIS. The sections on probabilistic methods and quantitative hazard and risk assessment have been expanded. New case studies and practical do's and don't's make this product a vital handbook for all those working in the field.